Biological artificial fluid-induced non-lamellar phases in glyceryl monooleate: the kinetics pathway and its digestive process by bile salts. (February 2014) - Zhou, Yanyan; Wang, Qifang; Wang, Yan; Xu, Hui; Yuan, Bo; Li, Sanming; Liu, Hongzhuo
Abstract Background: The cubic (QII) phase is a promising sustained-release system. However, its rigid gel-like propensity is highly viscous, which makes it difficult to handle in pharmaceutical applications. To circumvent this problem, a less viscous lamellar (Lα) phase that could spontaneously transform to QII phase by the introduction of water or biological artificial fluid can be used. However, the kinetics pathway of phase transition, susceptibility to digestive processes and impact of the transition on drug release are not yet well understood. Method: We investigated various biological artificial fluid-induced Lα to inverse QII phase transition over time in glyceryl monooleate (GMO) by water penetration scan and light polarizing microscopy. To reveal the structure stability, fluorescence spectroscopy studies were conducted using pyrene as a probe. Furthermore, the release mechanism of pyrene as a lipophilic drug model in the spontaneously formed QII was investigated. Result: Although hexagonal (HII) mesophases occurred when phosphate buffered saline (PBS) 7.4, 0.1 M HCl or sodium taurocholate (NaTC) solutions were introduced to GMO at room temperature, they disappear with the exception of 0.1 M HCl at 37 °C. Compared with 25 °C, Lα to QII phase transition was in a faster rate as almost completely transforms were observed after 2 h post-immersion. The spontaneously formed mesophases were stable over 24 h immersions in PBS or pancreatic lipase solutions as proven by the extremely low fluorescence signal, however they were digestible by bile salts. This result indicated that digestion by bile salts was the major pathway instead of digestion by lipases. Moreover, pyrene fluorescence spectroscopy confirmed that the digestion by bile salts induced the formation of GMO–bile salt mixed micelles whose performance depended on the bile salt concentrations. This dependence influenced the drug release from the spontaneously formed QII phase. Conclusion: All the results concluded that temperature, pH and ionic strength tendencies for the formation of non-lamellar structures greatly influenced the self-assembly process, thereby affecting the final mesophase structure. The results of this study are important to understand the lamellar to non-lamellar lipid-phase transitions and their possible pharmaceutical applications.